Intra-atrial re-entrant tachycardia in congenital heart disease: types and relation of isthmus to atrial voltage. Issue 2 (9th August 2017) - Roca-Luque, Ivo; Rivas Gándara, Nuria; Dos Subirà, Laura; Pascual, Jaume Francisco; Domenech, Antònia Pijuan; Pérez-Rodon, Jordi; Subirana, M Teresa; Santos Ortega, Alba; Miranda, Berta; Rosés-Noguer, Ferran; Ferreira-Gonzalez, Ignacio; Ferrer, Jaume Casaldàliga; et al.
Abstract: Background: Intra-atrial re-entrant tachycardia (IART) is a frequent and severe complication in patients with congenital heart disease (CHD). Cavotricuspid isthmus (CTI)-related IART is the most frequent mechanism. However, due to fibrosis and surgical scars, non-CTI-related IART is also frequent. Objective: The main objective of this study was to describe the types of IART and circuit locations and to define a cut-off value for unhealthy tissue in the atria. Methods and results: This observational study included all consecutive patients with CHD who underwent a first ablation procedure for IART from January 2009 to December 2015 (94 patients, 39.4% female, age: 36.55 ± 14.9 years, 40.4% with highly complex cardiac disease). During the study, 114 IARTs were ablated (1.21 ± 0.41 IARTs per patient). Cavotricuspid isthmus-related IART was the only arrhythmia in 51% ( n  = 48) of patients, non-CTI-related IART was the only mechanism in 27.7% ( n  = 26), and 21.3% of patients ( n  = 20) presented both types of IART. In cases of non-CTI-related IART, the most frequent location of IART isthmus was the lateral or posterolateral wall of the venous atria, and a voltage cut-off value for unhealthy tissue in the atria of 0.5 mV identified 95.4% of IART isthmus locations. Conclusion: In our population with a high proportion of complex CHD, CTI-related IART was the most frequent mechanism, although non-CTI-related IART was present in 49% of patients (alone or with concomitant CTI-related IART). A cut-off voltage of 0.5 mV could identify 95.4% of the substrates in non-CTI-related IART.